Species Dominance along Different Altitudes in Western Himalayan Forest of Langate Forest Division Kashmir, India - Bashir, Suhail; Dutt, Vaishnu; Magry, Muneer Ahmad (Indian Forester, 2021)
Due to biotic and abiotic factors, there is a continuous loss in floristic diversity and changing patterns of vegetation which have necessitated the qualitative and quantitative assessment of vegetation. This study aims at a floristic assessment of trees, shrubs, and herbaceous species at different altitudinal gradients (1500-2000, 2000-2500, 2500-3000m) for which the quadrate method was adopted. Altogether 44 plant species belonging to 16 families were found present in the study region. The results revealed that all altitudinal gradients (1500-2000m, 2000-2500m, 2500-3000m) varied in the dominance of species. Pinus wallichiana, Indigofera heterantha and Cynodon dactylon, in the lower altitudinal gradient (1500-2000m) and Pinus wallichiana, Cotoneaster falconeri and Dactylis glomerata were found dominant in the middle altitudinal gradient (2000-2500m) whereas Abies pindrow, Skimmia laureola and Poa pratensis was found as the principal association on the upper altitude (2500-3000m).